Pilot Study on Cyberbullying among Visually Impaired Youths - Ku, Wen Li; Ooi, Pei Boon *; Chan, Nee Nee * (MDPI, 2022)
Social networking has dominated the modern technological era, with youths being the main users. However, technological advancement has instilled a form of online violence called cyberbullying. Visually impaired Malaysian youths are no exception to cyberbullying incidents; however, this aspect has been understudied in Malaysia. This study examined the associated factors of cyberbullying among visually impaired Malaysian youths. A total of 30 participants were included in the Braille/pen-and-paper and voice-over online survey. We found that only aggressive behavior was positively associated with cyberbullying (ß = 0.544, p = 0.002). The distinctiveness of the study can help to draw public attention to the issue of cyberbullying.